Wilāyah and Ethical Excellence in Islam: An Ismā‘īlī Perspective - Khan, Mir Baiz (Islamic Studies, 2023)
Muslims across interpretations have in common ethical values and principles stemming from the Qur’ān. The first and foremost principle is to emulate the pattern of the Prophetic character as an ideal exemplar. The Qur’ān presents the character and nature of Prophet Muḥammad (peace be on him) as the best. On this Qur’ānic foundation, ethical excellence is sought, ethical issues are conceptualized, and frameworks are developed by Muslim scholars and religious authorities. With this common heritage, Muslim communities, however, expounded a variety of interpretations, particularly regarding the authority to interpret and determine the best emulation of the character and nature of the Prophet. Drawing on the Qur’ān and the life of the Prophet, this research seeks to investigate Islamic ethics from the shī‘ī and specifically the Ismā‘īlī perspective. The method applied in this article is an Islamic hermeneutic known as ta’wīl, which is interpreting the apparent words of the revelation (tanzīl) and seeking their inner meanings. Through this approach, the author shows how the ẓāhir (exoteric) symbolizes the bāṭin (esoteric) while inextricably being linked together.